Medication burden and clustering in people living with HIV undergoing therapeutic drug monitoring. Issue 11 (7th May 2021) - Calcagno, Andrea; de Nicolò, Amedeo; Pizzi, Costanza; Trunfio, Mattia; Tettoni, Cristina; Ferrara, Micol; Alcantarini, Chiara; Trentini, Laura; D'Avolio, Antonio; Di Perri, Giovanni; Bonora, Stefano
Abstract : Aim: People living with HIV (PLWH) have a high burden of comorbidities and concomitant medication use. The aim of this study was to analyse the prevalence, predictors and patterns of polypharmacy (PP) in a large therapeutic drug monitoring (TDM) registry. Methods: We searched our TDM registry and categorized co‐medications into 26 drug classes. We included patients with at least one medication recorded: PP and severe polypharmacy (sPP) were defined as the concomitant use of ≥5 or ≥10 nonantiretroviral/nonantitubercular drugs. Multivariable binary logistic analysis were conducted for identifying PP/sPP predictors. A hierarchical average‐linkage cluster analysis was performed among drug classes. Results: We included 2432 participants (1158 PLWH) aged 49.6 years (± 14.4) in the 2016‐2020 period. A higher number of concomitant medications (4 vs 3.1, P < .001) and a higher prevalence of PP (26.1% vs 21.8%, P = .015) were recorded in controls. At multivariable binary logistic analysis older age, female gender and HIV‐positive serostatus ( P = .015) were independent predictors of PP; older age and year of inclusion were independent predictors of sPP. Cluster analysis showed that patients receiving oral drug for type 2 diabetes have a high probability of receiving several other drugs; a cluster of co‐medications was observed with opioids, diuretics and central nervous system‐affecting drugs. Conclusion: We observed a moderately high prevalence of polypharmacy in middle‐aged PLWH: advanced age and female gender were associated with the greatest prevalence. The observation of co‐medication clusters suggests groups of comorbidities but also identifies groups of patients at risk of similar drug‐to‐drug interactions. Abstract :